Failure analysis of aircraft tubular form-fit joints in rotating-bending fatigue tests. (March 2023) - Yang, Jingchao; Men, Xiangnan; Rong, Peng; Cao, Jindou; Guo, Wei; Li, Guangjun; Li, Heng
Highlights: The tubing components composed of tubular form-fit joints are fabricated by elastomeric swaging. The platform for rotating-bending fatigue tests is established to simulate the high-frequency vibration of aircraft tubing components. The failure position of tubular form-fit joint causing the fatigue fracture is explored by numerical simulation. The failure mechanism of bending-torsion multiaxial fatigue crack initiation and propagation is revealed by SEM observation. Abstract: Tubular form-fit joints play a key role of connecting and sealing in the pipeline system of aircraft. However, they experience the complex fatigue behavior in operating conditions of compound excitation with internal fluid pulse pressure and external structural high-frequency vibration. To investigate the above fatigue behavior, the tubing component composed of tubular form-fit joints is fabricated by elastomeric swaging firstly; then the rotating-bending experimental platform for the tubing component is built to simulate the operating conditions in the above actual service period, and the rotating-bending fatigue (RBF) tests of tubing components under different deflections are carried out, so that the relationship between the fatigue strength and life is obtained; then, the bending-torsion multiaxial mechanical behavior of tubing component is analyzed when it is filled with constant internal pressure, bent at a deflection and rotated at a high speed in the RBF test. It can be found that the area near the sharp edge of sleeve groove is the most prone to crack initiation. Furthermore, the mechanism causing the fatigue fracture of tubing component is explored at the certain position of the joined tube by means of numerical simulation. Eventually, with the aid of scanning electron microscope, the mechanism of bending-torsion multiaxial fatigue crack initiation and propagation is revealed by fracture morphology observation and analysis. It can be found that the fatigue crack source on the outer wall of the joined tube is various, and the crack propagation direction is from the outer wall to the inner wall along the radial direction.